Environmental noise exposure and autoimmune diseases: Evidence from a national cohort study - Seunghyun Lee; Yongho Lee; Wanhyung Lee; Xiaoxue Ma (Ecotoxicology and Environmental Safety)
Exposure to environmental noise is an inevitable factor and may pose a risk to health conditions, even potentially affecting the immune system. However, the relationship between noise exposure and autoimmune diseases has not been well explored. This study aimed to investigate whether noise exposure is associated with an increased risk of autoimmune diseases in South Korea. We analyzed data from the National Health Insurance Service (NHIS) cohort from 2013 to 2019. Environmental noise data were provided by the National Noise Information System (NNIS) and spatially interpolated using empirical Bayes kriging (EBK) to estimate noise levels at the district level. Both daytime and nighttime noise were assessed, with mean noise exposure values calculated for each administrative district. The HR were estimated using the Cox proportional hazards model, along with standardized incidence ratios (SIRs) for autoimmune diseases. A trend analysis was also performed to examine the association between cumulative noise exposure and autoimmune disease incidence. High noise exposure was significantly associated with an increased risk of autoimmune diseases (HR 1.03; 95 % CI: 1.01–1.05), including higher SIRs for Rheumatoid Arthritis, Systemic Lupus Erythematosus, Hashimoto’s disease, and Graves’ disease. A significant trend was observed, with greater noise exposure correlating with higher autoimmune disease incidence, particularly for total and daytime noise. This study provides evidence of a significant association between high environmental noise exposure and increased risk of autoimmune diseases, indicating noise as a modifiable risk factor.